2013
DOI: 10.1016/j.jhazmat.2013.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Electrodialytic removal of Cd from biomass combustion fly ash suspensions

Abstract: h i g h l i g h t sElectrodialytic remediation could be used to remove Cd from biomass fly ash suspensions. Cd limiting concentrations in the fly ash were met for reuse as fertilizer. pH below 2 in the fly ash suspension was determining the effectiveness for Cd removal. a r t i c l e i n f o a b s t r a c tDue to relatively high concentrations of Cd, biomass combustion fly ashes often fail to meet Danish legislative requirements for recycling as fertilizer. In this study, the potential of using electrodialyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Despite the general belief in the beneficial impact of biomass ash on the environment, numerous research has indicated the presence of heavy metals in biomass ash, and their content depends primarily on the type of biomass burned [14]. Concentrations of metals in wood ash varies in wide ranges: Cd 1-41 mg/kg [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], Co 3-27 mg/kg [17, 19-21, 23, 27, 29], Cr 11-9914 mg/kg [15][16][17][20][21][22][23][24][25][26][27][28][29][30][31][32], Cu 13-8793 mg/kg [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]…”
mentioning
confidence: 99%
“…Despite the general belief in the beneficial impact of biomass ash on the environment, numerous research has indicated the presence of heavy metals in biomass ash, and their content depends primarily on the type of biomass burned [14]. Concentrations of metals in wood ash varies in wide ranges: Cd 1-41 mg/kg [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], Co 3-27 mg/kg [17, 19-21, 23, 27, 29], Cr 11-9914 mg/kg [15][16][17][20][21][22][23][24][25][26][27][28][29][30][31][32], Cu 13-8793 mg/kg [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]…”
mentioning
confidence: 99%
“…Previous experiments were conducted in the three/five-compartment cell on straw or wood ash separately [5,10,14,22]. Ottosen et al [10] conducted EDR experiments for 14 days at the current density of 0.8 mA cm -2 (corresponding to approximately 40 mA), and achieved removal of Cd of 75% and 45% from straw ash and wood ash, respectively.…”
Section: Overall Removalmentioning
confidence: 99%
“…Kirkelund et al [5] treated a straw fly ash and a pre-washed straw ash with high initial Cd concentrations of 19 and 64 mg kg -1 TS, respectively. They achieved a Cd concentration below 2 mg kg -1 TS in the raw straw fly ash after treatment at a L/S ratio of 7 and a current of 40 mA (equivalent to the current density of 0.8 mA cm -2 ) for 14 days.…”
Section: Overall Removalmentioning
confidence: 99%
See 2 more Smart Citations